2020
DOI: 10.1109/access.2020.3010863
|View full text |Cite
|
Sign up to set email alerts
|

Breast Lesion Classification in Ultrasound Images Using Deep Convolutional Neural Network

Abstract: In recent years, convolutional neural networks (CNNs) have found many applications in medical image analysis. Having enough labeled data, CNNs could be trained to learn image features and used for object localization, classification, and segmentation. Although there are many interests in building and improving automated systems for medical image analysis, lack of reliable and publicly available biomedical datasets makes such a task difficult. In this work, the effectiveness of CNNs for the classification of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…15 Recently, a radiomics study based on breast ultrasonography has shown good performance classifying breast benign and malignant lesions. 16,17 Because machine learning methods might appear in different performances when applied to different scenarios. 9,18,19 Therefore, it is necessary to explore the most appropriate feature selections and classifiers to construct the optimal radiomics model in various clinical fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Recently, a radiomics study based on breast ultrasonography has shown good performance classifying breast benign and malignant lesions. 16,17 Because machine learning methods might appear in different performances when applied to different scenarios. 9,18,19 Therefore, it is necessary to explore the most appropriate feature selections and classifiers to construct the optimal radiomics model in various clinical fields.…”
mentioning
confidence: 99%
“…Radiomics can be coupled with various imaging examinations, such as mammography, ultrasonography, computed tomography, and magnetic resonance imaging 15 . Recently, a radiomics study based on breast ultrasonography has shown good performance classifying breast benign and malignant lesions 16,17 . Because machine learning methods might appear in different performances when applied to different scenarios 9,18,19 .…”
mentioning
confidence: 99%
“…Briefly, images were imported, and the validation and training splits were generated followed by verification that the proper images were loaded using Matplotlib. The initial architecture of the algorithm was designed to include image augmentation and dropout regularization similar to previous research efforts to minimize overfitting 32 (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Deep learning based methods can overcome the limitations of traditional methods with their powerful feature extraction capability. Zeimarin et al 31 reported enhanced performance in tumor classification while using a custom CNN model with regularization technique. More than the custom-built CNN, several architectures which are trained on large dataset, can easily be fine tuned for classification of tumors.…”
Section: Related Workmentioning
confidence: 99%